Halal Industry in Thailand Presented in Bangkok Post: Structural Linguistics and World Englishes Perspectives - Pairote Bennui (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2026)
The halal industry is a contemporary global trend of economic development because of the growing number of Muslim consumers. This is realized in Thailand, although it is a Muslim-minority country. Research studies have been conducted to support the readiness of Thailand as a regional hub of the Halal industry. However, a few works emphasize English studies on Thailand’s Halal industry. Thus, this study aims to analyze lexical, grammatical, and semantic features of English regarding the Halal industry in the Bangkok Post, a leading English-language daily newspaper in Thailand. It also discusses the extent of the structural linguistic features that indicate and contribute to World Englishes in the Islamic context of the Thai and global economy. Based on the frameworks of morphology, grammar, semantics, and World Englishes using textual analysis, results revealed that the journalists utilized and constructed a range of outstanding lexical formations as well as phrases and clauses in English that incorporate Arabic and Thai and convey specific semantic features in order to present the Halal industry in Thai society. These structural linguistic features can indicate their Islamic English, World Englishes of global commerce/economy, and Thai Muslim identity of English.